2019
DOI: 10.7759/cureus.4799
|View full text |Cite
|
Sign up to set email alerts
|

Marijuana-induced Coronary Vasospasm with Persistent Inter-coronary Connection: A Case Report and Review of Literature

Abstract: Coronary vasospasm is a well-known entity causing acute chest syndrome and can lead to myocardial infarction, ventricular arrhythmias, and even sudden cardiac death. While there are extensive case series showing the association of coronary vasospasm with cocaine, studies reporting marijuana-induced coronary vasospasm are limited in number. We herein present a case of coronary vasospasm in a middle-aged African-American male who presented to the emergency department after an episode of syncope. His urine drug s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Although few case reports in the past have described coronary vasospasm, with this case report, we have tried to describe one of the rare cases of coronary vasospasm with significant troponin elevation in the setting of transient EKG changes [13]. In another case report, a patient with cannabinoid hyperemesis syndrome was reported to have STEMI with coronary vasospasm, without any troponin elevation, and Echo findings consistent with Takotsubu cardiomyopathy [14].…”
Section: Discussionmentioning
confidence: 97%
“…Although few case reports in the past have described coronary vasospasm, with this case report, we have tried to describe one of the rare cases of coronary vasospasm with significant troponin elevation in the setting of transient EKG changes [13]. In another case report, a patient with cannabinoid hyperemesis syndrome was reported to have STEMI with coronary vasospasm, without any troponin elevation, and Echo findings consistent with Takotsubu cardiomyopathy [14].…”
Section: Discussionmentioning
confidence: 97%
“…46,47 Finally, we also found that a higher percentage of patients with cannabis usage required mechanical thrombectomy (1.8%, compared with 1.6%), and presented with a higher risk of mortality (aOR: 5.169). As the consumption of cannabis can cause several cardiac arrhythmias, [44][45][46] vasospasms, 48 imbalances in coagulation, 7,49,50 protocols to monitor various possible side effects in such patients should be adopted. Furthermore, our study was unable to determine the outcomes of these patients' thrombectomy based on the centres' volumes, "doorto-groin" time, and the physicians' experience, which may have impacted the prognosis of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Marijuana is known to cause vascular endothelial dysfunction [19]. Multiple similar cases of STEMI [20,21,22,23] and NSTEMI related to marijuana induced have been reported in the past [24].…”
Section: Discussionmentioning
confidence: 99%